2000
DOI: 10.1088/0305-4470/33/9/303
|View full text |Cite
|
Sign up to set email alerts
|

Punctured polygons and polyominoes on the square lattice

Abstract: We use the finite lattice method to count the number of punctured staircase and self-avoiding polygons with up to three holes on the square lattice. New or radically extended series have been derived for both the perimeter and area generating functions. We show that the critical point is unchanged by a finite number of punctures, and that the critical exponent increases by a fixed amount for each puncture. The increase is 1.5 per puncture when enumerating by perimeter and 1.0 when enumerating by area. A refine… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
51
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(56 citation statements)
references
References 23 publications
(55 reference statements)
5
51
0
Order By: Relevance
“…We here provide hypergeometric solutions to the operators appearing in their linear ODEs. It has long been suspected that their generating functions are related to each other [7,8,9,11], and indeed we here show that they are equal up to the sum of an algebraic factor. Our hypergeometric solutions constitute the first example of a SAP generating function which is D-finite but not algebraic.We begin by reviewing the literature of staircase, three-choice, and punctured staircase polygons in section 2, followed by an analysis of the linear differential operators of the three-choice and punctured staircase polygon linear ODEs in section 3.…”
supporting
confidence: 65%
See 1 more Smart Citation
“…We here provide hypergeometric solutions to the operators appearing in their linear ODEs. It has long been suspected that their generating functions are related to each other [7,8,9,11], and indeed we here show that they are equal up to the sum of an algebraic factor. Our hypergeometric solutions constitute the first example of a SAP generating function which is D-finite but not algebraic.We begin by reviewing the literature of staircase, three-choice, and punctured staircase polygons in section 2, followed by an analysis of the linear differential operators of the three-choice and punctured staircase polygon linear ODEs in section 3.…”
supporting
confidence: 65%
“…Finally, it is possible to consider the effect of increasing the number of punctures for punctured staircase polygons. In [11], the effect of increasing the number of punctures was considered: it was found that as the number of punctures increases, the perimeter generating function critical exponent increases by 3/2 per puncture, while the area generating function critical exponent increases by 1 per puncture. In both cases, the critical point was found to be unchanged by a finite number of punctures.…”
Section: Towards Generalizations Of the Resultsmentioning
confidence: 99%
“…Using the CLN 5 library for c++, we computed a c (p) to 300 signiÿcant digits for p from 10 to 400, and then to 1000 digits for p from 1000 to 1100. Plotting this data and using the techniques described in [8,17], we reached the following hypothesis for the asymptotic behaviour of a c (p):…”
Section: Analysis Of {Ba P−1 } * Bmentioning
confidence: 88%
“…The generating function for staircase polygons with a staircase hole is also not known in closed form. Its properties are expected to be similar in many respects to the generating function for three-choice polygons [11]. We shall be concerned with self-reciprocity properties of the generating functions H m (y, q) that count polygons of width m. We first give two examples.…”
Section: Self-reciprocity In Polyomino Enumerationmentioning
confidence: 99%